Graphene oxide decoration with ZnAl LDH and further functionalization with APTES for enhancing the toughness of polyurethane coatings - Ashkan Aslani; Hossein Yari; Mahmood Rezaei; Mohammad Ramezanzadeh; Mostafa Jalili; Bahram Ramezanzadeh (Scientific Reports)
Abstract The primary goal of this study is the enhancement of the mechanical properties of polyurethane (PU) coating via introducing a hybrid sandwich-like nanofiller composed of layered double hydroxide (LDH) grown on graphene oxide. To increase the nanofiller compatibility with the PU matrix, its surface was functionalized with an amino-functional silane coupling agent(APTES). Characterization of the particles with Raman, TGA, EDX-mounted FESEM, XRD approved the prosperous synthesis and modification of the nanosheets. The untreated (LDH@GO) and silane-treated (LDHGO@Si) nanoplatelets at three loading levels (1, 2, and 3 wt%) were incorporated and the stress-strain behavior of various nanocomposites films were evaluated. The stress-strain diagrams revealed that there is an optimum content (2wt.%) for both nanosheets that causes a rise in mechanical properties. While LDH@GO could improve the toughness of the PU by 95%, the treated counterpart (LDHGO@Si) resulted in a stronger impact, leading to a 184% rise concerning unfilled PU (from 1.27 to 3.6 GPa) in toughness thanks to its better dispersion, more extensive covalent and non-covalent interactions with PU chains. DMTA results also depicted that the treated nanosheets formed a reinforced network with increased Tg and crosslinking density that can efficiently delocalize the stress under tensile pressure, resulting in promoted energy dissipation and toughness.